Siva-Buddha And Tantric Value In Calon Arang Tradition - I Made Suastika; Luh Putu Puspawati (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2020)
Calon Arang has a complex values in Bali. This can be seen from the number of Calon Arang manuscripts (texts) stored in various places in Bali, including in the institutions of the Faculty of Literature, Gedong Kirtya, and abroad in the Netherlands. For the purpose of this study which is to obtain the authentic and oldest Calon Arang text, the tracking was carried out to these places using the method of text study (Philology). With the aim to that values in the text of Calon Arang can be understood, it is therefore necessary to understand the value of the text as contained in the text of Candidate Arang Lor 5387/5279 which dates to 1540AD, namely in the Gelgel era, the oldest discovered during this research. Calon Arang harbor the Hindu Buddhist cultural and religious values of his day so it is important to express the Shiva-Tantric and Buddhist values contained in the text with the content analysis method. The findings obtained from the study of the text of Calon Arang is varied and it was copied from time to time. Base on philology findings the text of Calon Arang 1540 AD contains cultural and religious values in the Gelgel era, namely Tantric-Shiva and Buddhism. That values live and develop up to now as a breath of Hinduism and Balinese culture which is known to be sacred and religious as seen in the storyline and dialogue of Buddhist Mpu Beradah with all of its students such as Calon Arang, Lenda, Lendi, Guyang, Larung and to the King Erlangga.